Research Article Chronic Subdural Hematoma in Khost - Lakanwal, Qaiswer Shah (Journal for Research in Applied Sciences and Biotechnology, 2023)
In this study, chronic subdural hematoma patient investigated and information related to chronic subdural hematoma collected, the CSDH described briefly, this study was conducted in different hospital in khost province, information related to age, gender, causes, clinical manifestation, and hematomae location has been collected.